1999
DOI: 10.1074/jbc.274.24.16701
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Metabolic Alterations in Mice Lacking Both β1- and β2-Adrenergic Receptors

Abstract: The activation state of ␤-adrenergic receptors (␤-ARs) in vivo is an important determinant of hemodynamic status, cardiac performance, and metabolic rate. In order to achieve homeostasis in vivo, the cellular signals generated by ␤-AR activation are integrated with signals from a number of other distinct receptors and signaling pathways. We have utilized genetic knockout models to test directly the role of ␤1-and/or ␤2-AR expression on these homeostatic control mechanisms. Despite total absence of ␤1-and ␤2-AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
185
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(208 citation statements)
references
References 43 publications
13
185
1
4
Order By: Relevance
“…For this purpose we evaluated the skeletal response to loading by axial compression in Adrb1 À/À , Adrb2 À/À , and Adrb1b2 À/À double knockout mice and we further characterized the mechanisms by which b1-adrenergic receptors and b2-adrenergic receptors may regulate bone mass and microarchitecture. (24) Our results indicate that b1-adrenergic receptors and b2-adrenergic receptors exert opposite effects on bone remodeling through both systemic and local factors.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…For this purpose we evaluated the skeletal response to loading by axial compression in Adrb1 À/À , Adrb2 À/À , and Adrb1b2 À/À double knockout mice and we further characterized the mechanisms by which b1-adrenergic receptors and b2-adrenergic receptors may regulate bone mass and microarchitecture. (24) Our results indicate that b1-adrenergic receptors and b2-adrenergic receptors exert opposite effects on bone remodeling through both systemic and local factors.…”
mentioning
confidence: 67%
“…Adrb1b2 À/À mice were on a mixed 129 SvJ, FVB/N, C57BL/6J genetic background. (24) Mice were maintained under standard non-barrier conditions and had access to mouse chow (RM3; SDS, Surrey, UK) and water ad libitum.…”
Section: Animals and Experimental Proceduresmentioning
confidence: 99%
“…Alteration of gene expression and responsiveness of other receptors and their effectors have been reported in numerous genetic knock out mice. For instance, mice deficient in both β 1 -and β 2 -adrenergic receptors show an exaggerated response to a β 3 agonist [24] as well as enhanced dopamine function was found in 5-HT1B receptor knockout mice [25]. Also, in the absence of nNOS, eNOS was able to somehow change its expression to compensate for the loss of nNOS [26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that b 2 -adrenoceptors, which are the main b-adrenoceptor subtype responsible for the vasodilator response induced by nonspecific b-agonists (O' Donnell & Wanstall, 1984), are less susceptible than b 1 -adrenoceptors to downregulation (Cohen & Schenck, 1987). In addition, b 3 -adrenoceptors can be upregulated when b 1 -and b 2 -adrenoceptor subtypes are downregulated (Rohrer et al, 1999;Moniotte et al, 2001). Moreover, it is known that high doses of ISO and other catecholamines can induce toxic effects (Balta et al, 1995;Banerjee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%